General comparison of the electrical transportation systems that are fed with 1X25kV or 2X25kV and expectations from these systems - Senol, I; Gorgun, H; Aydeniz, MG (IEEE, 1998)
In electrical transportation systems which are fed from interconnected a.c. network, the voltage of the conductor is 25kV, frequence is 50 Hz or 60Hz. Power need depends on the number of the cars and the density of traffic. In modern fast trains it can be seen that the power is 12-15 MW per car. Beside technical wants, all system's economy is an important concept. Providing of energy of high power traffic a) With returning conductor in1x25kV systems b) With auto transformer in 2x25kV systems If there is no added returning conductor in 1x25kV systems, there will be some unwilling effects between transportation system conductor and signalization conductor. The current which passes over earth to substation causes these effects. There is conductor that is serial connected with transformers, in order to limit this returning current so this current pass over this conductor. When the line current increases, the voltage drop quiete increases. We assume that phase disconnectionplace which necessary for interconnected network feeding is next to substation for comparison of both basic systems. In this condition, substation transformers are connected with three phase network, so asymmetrical load of interconnected a.c. networks can be decreased. Neutral areas usually are placed between two wired station in free way.
Keywords: Automation & Control Systems; Computer Science; Engineering; Optics; Telecommunications